Edukasi Gizi Berbasis Video Singkat: Meningkatkan Sikap dan Perilaku Ibu dalam Pemberian Makan Balita: Short Video-Based Nutrition Education: Enhancing Mothers’ Attitude and Behaviors in Toddlers Feeding - Ferestha, Reyfika Diva; Christa, Theresa Angelina; Muniroh, Lailatul (Amerta Nutrition, 2026)
Background: Adequate nutrition for toddlers aged 3-5 years is essential for optimal growth and development, while improper feeding practices increase the risk of malnutrition and stunting. According to the 2024 Indonesian Nutrition Status Survey. Nutrition education for mothers is a key preventive strategy, with short videos considered more engaging and accessible. Objectives: This study aimed to evaluate the impact of short videos on mothers’ attitudes and behaviors in feeding aged toddlers 3-5 years at Kalirungkut Health Center, Surabaya. Methods: A quasi-experimental design with pre-test and post-test was applied to 62 mothers of toddlers, selected through simple random sampling. Participants were divided into an intervention group (short videos) and a control group (PowerPoint). Data on attitudes and feeding behaviors were collected using validated questionnaires and analyzed with Paired t-test and Wilcoxon Signed Rank Test. Results: Significant improvements were observed in mothers’ attitudes and behaviors after the short video intervention. Attitude scores increased from 59.71±6.095 to 65.84±3.067 (p-value<0.001), while behavior scores rose from 70.78±3.574 to 78.39±2.679 (p-value<0.001). In the control group, no significant changes were found in either attitudes (p-value=0.43) or behaviors (p-value=0.174). Conclusions: Short video-based nutrition education is more effective than PowerPoint in improving mothers’ attitudes and behaviors in toddler feeding. Short videos are practical, engaging, and highly recommended as tools for community nutrition education and public health promotion.